La Lectio Divina desde la acción humana (2016)
One of the most appropriate ways to love the Bible is the practice of Lectio Divina. This prayerful reading of the Bible has the imprint of the Fathers of the Church and has been cultivated over the centuries in the heart of the monastic life. Currently, this practice is being rediscovered with great enthusiasm to promote the spiritual life of religious communities and spiritual food of all the baptized in the different ecclesial communities (DV, 25). In Sacred Scripture “God comes to meet us to speak to us” (DV, 21) and, therefore, the best way to make a productive reading of the Bible is the prayerful reading. Hence, it is important an attitude of sincere faith and a desire to enter into conversation with God, according to what we read and what grace put us at the heart and at all times.